Modulation of Illusory Auditory Perception by Transcranial Electrical Stimulation - Prete, Giulia; D'Anselmo, Anita; Tommasi, Luca; Brancucci, Alfredo (Frontiers in Neuroscience, 2017)
The aim of the present study was to test whether transcranial electrical stimulation can modulate illusory perception in the auditory domain. In two separate experiments we applied transcranial Direct Current Stimulation (anodal/cathodal tDCS, 2 mA; N = 60) and high-frequency transcranial Random Noise Stimulation (hf-tRNS, 1.5 mA, offset 0; N = 45) on the temporal cortex during the presentation of the stimuli eliciting the Deutsch's illusion. The illusion arises when two sine tones spaced one octave apart (400 and 800 Hz) are presented dichotically in alternation, one in the left and the other in the right ear, so that when the right ear receives the high tone, the left ear receives the low tone, and vice versa. The majority of the population perceives one high-pitched tone in one ear alternating with one low-pitched tone in the other ear. The results revealed that neither anodal nor cathodal tDCS applied over the left/right temporal cortex modulated the perception of the illusion, whereas hf-tRNS applied bilaterally on the temporal cortex reduced the number of times the sequence of sounds is perceived as the Deutsch's illusion with respect to the sham control condition. The stimulation time before the beginning of the task (5 or 15 min) did not influence the perceptual outcome. In accordance with previous findings, we conclude that hf-tRNS can modulate auditory perception more efficiently than tDCS.